1990
DOI: 10.1093/carcin/11.8.1287
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl chloride-induced DNA adducts II: Formating and persistence of 7-(2'oxoethyl)guanine and N2 ,3 ethenoguanine in rat tissue DNA

Abstract: The formation and persistence of the DNA adducts 7-(2'-oxoethyl)guanine (OEG) and N2,3-ethenoguanine (EG) were investigated in preweanling Sprague-Dawley rats exposed to vinyl chloride (VC). Lactating female CD rats with 10 day old pups were exposed to 600 p.p.m. VC by inhalation for 5 days, 4 h/day. Groups of rats were killed immediately and 3, 7 and 14 days after exposure. The concentrations of OEG and EG were measured in liver, lung, kidney, brain and spleen. HPLC with fluorescence detection was used for OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 0 publications
2
123
0
2
Order By: Relevance
“…7-(2'-Oxoethyl)guanine and three etheno adducts (-A; £C; and N2,3-EG; Figure 2) have been detected in DNA from rats and mice exposed to VC (123,(128)(129)(130)(131). Highly variable background levels ofcA and -C were found in all the tissues examined (132,133).…”
Section: Vc Initiation Of Hepatocarcinogenesismentioning
confidence: 95%
“…7-(2'-Oxoethyl)guanine and three etheno adducts (-A; £C; and N2,3-EG; Figure 2) have been detected in DNA from rats and mice exposed to VC (123,(128)(129)(130)(131). Highly variable background levels ofcA and -C were found in all the tissues examined (132,133).…”
Section: Vc Initiation Of Hepatocarcinogenesismentioning
confidence: 95%
“…81,82 There are also other exocyclic DNA adducts that arise from lipid peroxidation. For example, ethenodA, etheno-dC and etheno-dG have been detected by both 32 phospho-postlabeling and GC-MS. 83 It has been demonstrated that etheno-dA and etheno-dC are strongly genotoxic but weakly mutagenic when introduced on single-stranded vectors in E. coli. In addition, hydroxypropanodeoxyguanosines are present in human DNA in presence of cancer.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…The ⑀ DNA adducts were subsequently recognized as reaction products of DNA with reactive metabolites of several genotoxic chemicals, including the carcinogens vinyl chloride and vinyl carbamate (an oxidation product of urethane). The detection of etheno DNA adducts in various tissues of unexposed rodents (22) and humans (23) led to the discovery of the endogenous pathways of formation (e.g. via reaction with trans-4-hydroperoxy-2-nonenal, a lipid peroxidation product (24)).…”
mentioning
confidence: 99%